Product cannibalization and the effect of a service strategy. Issue 3 (4th March 2018) - De Giovanni, Pietro; Ramani, Vinay
Abstract: Product cannibalization can push some consumers to shift their purchasing preferences from new to used products. This is a costly issue for manufacturers, who have to adjust their pricing strategies accordingly to mitigate the negative effect of cannibalization. In this paper, we characterize an atypical channel to examine the effect of product cannibalization within the DellReconnect project. In particular, we investigate how the presence of a Goodwill agency in a second-hand market impacts the business of a manufacturer (e.g., Dell) in a new market through cannibalization, and how the manufacturer reacts to mitigate its effects. We show that even if the manufacturer adjusts its price to decrease the negative effects of cannibalization, this effect is so severe that it always loses some profits. Nevertheless, when the manufacturer provides some additional services to new consumers, the negative effects of cannibalization can be partially overcome.